Potencial produtivo de sementes florestais nativas para a restauração da Bacia do Rio Doce - Perussi, Gabriel (Universidade Federal de São Carlos, 2021)
i. After Mariana´s dam environmental disaster, with the overflow of Fundão tailings dam, the Doce river basin was heavily impacted, both socially and environmentally. As a way to restructure and recover regional conditions, a community network of seeds and seedlings in the Doce River basin (RBRD) is currently being consctruced. The objective of this work was to evaluate the structure and current capacity of seed collection and production of seedlings of native species and generate forecasts analyzing what is the necessary structure to reach the restoration demands foreseen in the Term of Transaction and Conduct Adjustment (TTAC), until 2030. For the collection of data on current productive capacity, data from the purchase of seeds from mobilized groups that will participate in the RBRD was used in its first year of operation (2019-2020), and applying the information in forecast models described by Urzedo et al. (2020). The results show that, to meet the demand of more than 27 thousand hectares restored by 2030, approximately 315.88 to 503.28 tons of seeds will be needed, varying according to the quality of the seeds collected for use in restoration through direct sowing techniques and planting of seedlings. It is also estimated that around 723 to 1129 collectors are mobilized and trained to supply these seeds.
Productive potential of native forest seeds for the restoration of the Doce River Basin
Keywords: semeadura direta; produção de sementes; tecnologia de sementes; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE UNIDADES EDUCATIVAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS BIOLOGICAS::ECOLOGIA